Michael Harris, Mathematics without apologies: portrait of a problematic vocation, Princeton University Press, Princeton, NJ, 2015, xxii+438, ISBN: 978-0-691-15423-7/hbk; 978-1-400-85202-4/ebook. - MOCANU, P. T. (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
This is an unusual book written by an eminent professional mathematicians,a well known expert in number theory and algebraic geometry. It reects author'sopinions on mathematics, both pure and applied, and on mathematicians, as seenfrom the inside of the caste and from outside as well. The author combines his ownexperience as a mathematician with that obtained from various domains of the humanknowledge - philosophy (Plato, Archimedes, Omar Khayam, hindustan philosophy,Witgenstein, Pascal, Russel Kant, Nietsche, etc), literature (a lot of quotations forGoethe's Faust and from Shakespeare), history, religion (the case of Pavel Florensky),cinematography and even pop music.